The comedian [videorecording (DVD)] - De Niro, Robert; Mann, Leslie, 1972-; DeVito, Danny; Falco, Edie; Ferres, Veronica, 1965-; Grodin, Charles; LuPone, Patti; Leachman, Cloris; Smith, Lois, 1930-; Keitel, Harvey (Sony Pictures classics., 2017)
A look at the life of an aging insult comic named Jack Burke.